Does smoking affect gingival crevicular fluid LL-37 levels following non-surgical periodontal treatment in chronic periodontitis?. (January 2016) - Türkoğlu, Oya; Eren, Gülnihal; Emingil, Gülnur; Azarsız, Elif; Kutukculer, Necil; Atilla, Gül
Highlights: LL-37 levels in periodontal health were similar between smoker and non-smokers. Smoker periodontitis patients had lower LL-37 levels than non-smokers counterparts. Periodontal treatment decreased LL-37 levels in non-smoker periodontitis patients. Periodontal treatment did not affect LL-37 levels in smoker periodontitis patients. Abstract: Objective: LL-37 contributes to maintaining the balance between health and disease. Smoking is a risk factor for periodontitis that impairs neutrophil functions. The aim of the present study was to comparatively evaluate gingival crevicular fluid (GCF) LL-37 levels in smoker and non-smoker chronic periodontitis (CP) patients and controls, as well as the effect of non-surgical periodontal treatment on GCF LL-37 levels. Design: Thirty-one CP patients (16 smokers, 15 non-smokers) and thirty-one controls (16 smokers, 15 non-smokers) were included in the study. CP patients received non-surgical treatment. GCF LL-37 levels and periodontal parameters were assessed at baseline, 1 and 3 months after completion of non-surgical periodontal treatment. GCF LL-37 levels were analyzed by ELISA. Results: No significant difference was observed in GCF LL-37 levels between smoker and non-smoker controls ( p  > 0.05). Smoker CP group had significantly lower GCF LL-37 level than non-smoker CP group at baseline ( p  < 0.05). GCF LL-37 levels significantly decreased in non-smoker CP group at first week, 1 and 3 months after completion of non-surgical periodontal treatment ( p  < 0.05) although no significant decrease in GCF LL-37 levels was observed in smoker CP group ( p  > 0.05). Periodontal parameters were correlated with GCF LL-37 levels in non-smoker CP group ( p  < 0.05), but not in smoker CP group ( p  > 0.05). Conclusions: GCF LL-37 levels do not seem to be affected from smoking in periodontal health. However, smoking might have a suppressive effect on GCF LL-37 levels in CP. Non-surgical treatment is effective in decreasing GCF LL-37 levels in non-smoker CP patients but not in smokers with CP.